Carbon fibre reinforced epoxy implants for bridging large osteoperiosteal gaps - Prakash R.; Marwah S.; Goel S.C.; Tuli S.M. (My University, 2025)
An experimental study was undertaken to evaluate the suitability or otherwise of carbon fibre reinforced epoxy (CFRE) implants for bridging large osteoperiosteal gaps, devoid of periosteum. Using the basic principles of composite mechanics and simple design criteria, CFRE implants were designed and developed. These implants were put in simulated osteoperiosteal gaps in the ulna of healthy mature rabbits. Ten wk postoperative results clearly demonstrated that implants made of CFRE induced callus bone formation (in the form of woven bone) which totally encapsulated the implant thereby providing reunion of the two bone segments. Further follow-up showed formation of lamellar bones and formation in the pores of the implant. Radiological and scanning electron microscopical evidence is presented. © 1988.